i-Locate - Indoor/Outdoor location and Asset Management through Open Data (GEOmedia, 2015)
Studi recenti hanno evidenziato che, in media, trascorriamo circa il 90% del nostro tempo in ambienti chiusi e, spesso, non familiari. L'esigenza di localizzare/guidare persone o ogg etti in spazi sia esterni che interni (senza discontinuità  tra esterno ed interno) darà  origine ad una serie di nuovi servizi di tipo LBS (Location-Based Services) che potranno avere anche una notevole rilevanza economica.i-locate (Indoor / outdoor location and Asset Management Through open geodata) is a project that aims to develop a set of tools and services based on geo location technologies based on open data for the location and management of objects in indoor and outdoor spaces. The tools are intended both to citizens who use their smartphones to access services, aids to navigation from the front door to internal destinations to buildings (public office, clinic, shop, etc.). Obtaining any information available to support (code , unforeseen changes in the path, suggestions, etc.), and professionals for specific activities that require the location of people, equipment, etc. i-locate to an intense use of GIS technologies for navigation and tracking "indoor" (indoor GIS, 3D GIS), to locate people (eg. Alzheimer's patients) and their movements in areas not suited (geofencing) to identify and track objects / portable equipment for their location, management and maintenance.